MASALAH DAN PROSPEK STUDI PSIKOLOGI ISLAM - Hayati Isma Nasution; Ubabuddin Ubabuddin (ADIBA : JOURNAL OF EDUCATION, 2024)
Islamic psychology is a study approach in understanding the human psyche and behavior based on the concept of monotheism, by integrating science and faith. Then it is made into a learning activity that becomes the most basic activity that leads to achieving educational goals, and the learning process and experience, as well as interests and ideals vary depending on the social structure of society in the field of psychology. Islamic psychology emphasizes learning, namely the process of behavioral change. This paper aims to explain and analyze Islamic psychology in terms of the problem of accepting a psychological science in Islam. Furthermore, it also explains the challenges and factors behind the presence of Islamic psychology. And how are the prospects of Islamic psychology.